APPLICATION OF THE VILLAGE FINANCIAL SYSTEM IN THE FINANCIAL MANAGEMENT OF PELEMWATU VILLAGE - Nisfatul Laili; Khalimatus Sa'diyah; Ernestiana Kebabu (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
The village financial system (SISKEUDES) is an application used by villages in the administrative budgeting process and village financial reporting. The village financial system (SISKEUDES) automatically generates various necessary reports so as to save time and costs, reduce the potential for fraud and errors, and help data aggregation. This study aims to analyze the implementation of the Village Financial System (SISKEUDES) on financial management in Pelematu Village, sub-district Menganti, Gresik Regency. This research uses qualitative data. The sampling technique uses Purposive Sampling. The result showed that: (1) The implementation of Village Financial System in Suwaan Village has running well (2) The procedure of SISKEUDES utilization done by 4 stages which are : Planning, Implementing, Administrating, and Reporting (3) Village Financial System has been giving the positive influence towards the performance of each employee.Keywords : Village Financial System, Village Finance